Microbial and Heavy Metal Contamination of Commercial Potash Solution (Ngor) in Some Parts of Eastern Nigeria - Udujih, Helen Ifeoma; Osuoha, C.; Dike-Ndudi, J. N.; Udujih, O. G. (British Journal of Healthcare and Medical Research, 2023)
Bacteria, heavy metal contamination of commercial ngor (potash solution) were assessed using culture, microscopy and biochemical characterization for bacterial detection, identification and quantification. Atomic absorption spectrophotometric (AAS) method was used for the determination of heavy metals. Results of this study showed bacterial and heavy metal contamination of commercially made potash solutions (Ngor). Out of the 50 potash solutions (Ngor) purchased from the various markets, 32 yielded significant bacterial growths. The total mean bacterial counts (cfu/ml) in the potash sample solution from the various markets in Imo and Abia state, were within the WHO permissible limits for water bacteria count. The following heavy metals were determined from the samples; Lead (Pb) Copper (Cu), Cadmium (Cd), Aluminium (Al), Nickel (Ni), Chromium (Cr), Mercury (Hg), Zinc (Zn), Cobalt (Co), Iron (Fe) and Manganese (Mn). Most of them (81.82%) had mean concentration that were higher and statistically significant when compared to the control (P<0.05). They were above the WHO permissible limits except Copper (Cu) from Orieugba, Nkwoegwu and Afor-Ogbe market and lead (Pb) from Nkwoegwu market. It is therefore necessary that clean water should always be used in preparation of food by both vendors and consumers. Agricultural practices that lead to increased levels of heavy metals in the soil should be curtailed.